A kind of water-based anticorrosive epoxy resin emulsion and its preparation method and application
Through the preparation method of modified epoxy resin emulsifier, the aqueous anticorrosion epoxy resin emulsion is prepared by the reverse method, which solves the problem of insufficient stability and anticorrosion performance of aqueous epoxy resin emulsion in the marine environment in the prior art, and realizes the realization of the problem of insufficient stability and anticorrosion performance of aqueous epoxy resin emulsion in the prior art. Coatings with high stability and good corrosion resistance.
Patent Information
- Application Number
- CN202411822771.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-12
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-12-12
AI Technical Summary
When existing aqueous epoxy resin emulsions are used in marine environments, the stability and corrosion resistance of the coating are insufficient, making it difficult to meet the strict metal marine corrosion requirements.
通过将双酚A型液态环氧树脂与二异氰酸酯化合物在催化剂作用下加热反应,加入聚乙二醇(PEG4000与PEG6000的混合物)进行改性,形成支链型改性环氧树脂乳化剂,并 The aqueous anticorrosion epoxy resin emulsion was prepared by mixing it with water by the reverse method.
The prepared water-based anti-corrosion epoxy resin emulsion has high stability, good corrosion resistance, strong coating adhesion, excellent impact resistance and moisture and heat resistance, and is suitable for metal marine anti-corrosion fields.
Smart Images

Figure CN119286356B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water-based coatings, and in particular to a water-based anticorrosive epoxy resin emulsion and a preparation method and application thereof. Background Art
[0002] The information disclosed in the background of the invention is only intended to enhance the understanding of the overall background of the invention and should not be necessarily regarded as an acknowledgment or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Metal corrosion in marine environments can cause huge economic losses. Electrochemical corrosion is the most common type of corrosion at sea and is also one of the most influential types of corrosion. There are currently two basic strategies for dealing with electrochemical corrosion: metal plating and organic coating. Among them, organic coatings are widely used in metal corrosion protection because of their high efficiency, economy, and environmental protection. Organic coatings act on metal substrates and can be regarded as a physical barrier to separate the corrosive liquid from the metal substrate, which can effectively slow down the corrosion rate of metals. However, under the long-term high-intensity influence of low pH, high humidity, high oxygen content, and high electrolyte content in the marine environment, the internal structure of the organic coating will produce defects such as pores, and the barrier efficiency will greatly decrease over time, resulting in direct contact between the corrosive agent and the metal substrate.
[0004] Epoxy resin has good chemical resistance and mechanical strength, as well as good thermal stability, which can effectively prevent water, oxygen, chloride ions, etc. from penetrating the coating to the surface of the metal structure and causing corrosion. However, after the epoxy resin is cured, its porosity, high strength, and high brittleness greatly limit the application and development of epoxy resin in anti-corrosion. In addition, with increasingly stringent environmental protection requirements, solvent-based epoxy resin coatings are gradually being phased out, and water-based epoxy resin coatings are increasingly being used in the field of marine anti-corrosion.
[0005] Waterborne epoxy resin emulsion is a key component of waterborne epoxy resin coating. At present, the methods used to prepare waterborne epoxy resin emulsion mainly include mechanical method, chemical method and phase inversion method. The mechanical method has complicated steps and requires additional grinding equipment. In addition, the latex particles obtained are large in size and have poor stability. Although the chemical method can obtain smaller latex particles with higher stability, the method has high preparation cost, complex process, difficult reaction control and more by-products. The phase inversion method is simple to operate and easy to implement, but the performance of the emulsion prepared by this method will be affected by the emulsifier to a large extent. At present, the emulsifier of the phase inversion method of waterborne epoxy resin usually uses epoxy resin as the hydrophobic segment and polyether alcohol as the hydrophilic segment. The epoxy resin emulsifier is prepared by the reaction of epoxy group ring opening with polyether alcohol, which not only consumes epoxy groups, resulting in a decrease in the density of the cross-linked coating, but also the free ester group will reduce the water resistance of the coating. At the same time, the corrosion resistance is poor, which makes it difficult to meet the application requirements in the field of metal marine corrosion protection with a relatively harsh application environment.
[0006] Therefore, how to provide a method for preparing water-based epoxy resin emulsion by phase inversion method so that the obtained water-based epoxy resin emulsion has comprehensive properties such as high stability, good corrosion resistance, coating adhesion, impact resistance and moisture and heat resistance is an urgent problem to be solved. Summary of the invention
[0007] In view of this, the present invention provides a water-based anti-corrosion epoxy resin emulsion and a preparation method and application thereof. The water-based anti-corrosion epoxy resin coating provided by the present invention has good comprehensive properties and has good application prospects in the field of metal corrosion protection.
[0008] In a first aspect, the present invention provides a method for preparing a water-based anticorrosive epoxy resin emulsion, comprising the following steps:
[0009] The bisphenol A type liquid epoxy resin and the diisocyanate compound are heated to react under the action of a catalyst, and then polyethylene glycol is added to react to obtain a modified epoxy resin emulsifier; the polyethylene glycol is a mixture of PEG4000 and PEG6000, and the mass ratio of PEG4000 to PEG6000 is 3:(1-3);
[0010] The modified epoxy resin emulsifier and bisphenol A type liquid epoxy resin are heated and mixed, and then water is added by a phase inversion method to prepare a water-based anticorrosive epoxy resin emulsion.
[0011] Preferably, the bisphenol A type liquid epoxy resin is selected from one or both of epoxy resin E44 and epoxy resin E51; the diisocyanate compound is selected from one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate or 4,4-dicyclohexylmethane diisocyanate; and the catalyst is selected from one or more of triphenylphosphine, boron trifluoride complex, tetrafluoroboric acid solution or tin tetrachloride.
[0012] Furthermore, the bisphenol A type liquid epoxy resin is selected from epoxy resin E44; the diisocyanate compound is selected from 4,4-dicyclohexylmethane diisocyanate, and the catalyst is selected from boron trifluoride etherate.
[0013] Preferably, the ratio of the molar amount of hydroxyl groups of the bisphenol A liquid epoxy resin, the molar amount of isocyanate groups of the diisocyanate compound, and the molar amount of hydroxyl groups of the polyethylene glycol is 1:(1.8-2.2):(0.9-1.5); and the added amount of the catalyst is 0.2-0.5wt%.
[0014] In the polyethylene glycol of the present invention, the mass ratio of PEG4000 to PEG6000 is 3: (1-3), more preferably 3: 2. Too much PEG4000 content will lead to decreased antiseptic performance and emulsion stability, and too much PEG6000 content will increase the system viscosity and reduce reactivity, thereby reducing the emulsification performance of the obtained modified epoxy resin emulsifier, which is not conducive to the subsequent phase inversion process.
[0015] Preferably, the reaction temperature of the bisphenol A type liquid epoxy resin and the diisocyanate compound is 80-100° C., and the reaction time is 2-8 hours.
[0016] Preferably, in the step of adding polyethylene glycol to react to obtain the modified epoxy resin emulsifier, the reaction temperature is 70-90° C. and the reaction time is 2-8 hours.
[0017] Preferably, in the step of heating and mixing the modified epoxy resin emulsifier and the bisphenol A type liquid epoxy resin, the mass ratio of the modified epoxy resin emulsifier to the bisphenol A type liquid epoxy resin is 1:(4-6).
[0018] The present invention does not impose any special restrictions on the specific process of the phase inversion method, and the solid content of the finally prepared water-based anticorrosive epoxy resin emulsion is controlled to be 30-50wt%.
[0019] In a second aspect, the present invention provides a water-based anticorrosive epoxy resin emulsion prepared by the above preparation method.
[0020] In a third aspect, the present invention provides an application of the above-mentioned water-based anticorrosive epoxy resin emulsion, wherein the application is an application in preparing a metal anticorrosive coating, and the method for preparing the metal anticorrosive coating is as follows:
[0021] The water-based anti-corrosion epoxy resin emulsion and the curing agent are evenly mixed and then coated on the surface of the metal substrate. After curing, the metal anti-corrosion coating is obtained.
[0022] The present invention does not impose any special restrictions on the type of curing agent, coating method and curing time, and the curing agent, coating method and curing method commonly used in the art can be used.
[0023] Compared with the prior art, the present invention has achieved the following beneficial effects:
[0024] (1) The present invention first prepares a branched modified epoxy resin emulsifier through a two-step reaction, then mixes it with an epoxy resin, and prepares a water-based anticorrosive epoxy resin emulsion by a phase inversion method. The preparation method is simple, does not require special equipment and complex reaction steps, and is suitable for mass production.
[0025] (2) The present invention uses a diisocyanate compound as a bridge. The isocyanate group at one end of the diisocyanate compound can undergo an addition reaction with the hydroxyl group in the liquid epoxy resin, and the polyethylene glycol then reacts with the unreacted isocyanate group. The reaction of the hydroxyl group of the polyethylene glycol with the isocyanate group takes precedence over the ring-opening reaction with the epoxy group, thereby reducing the consumption of the epoxy group, thereby improving the water resistance and density of the coating. At the same time, the polyethylene glycol in the present invention has a suitable molecular weight, which can provide good coating and strong hydrogen bonding to the epoxy resin molecules. The interaction between the polyethylene glycol and the water can make it stably dispersed. During the phase inversion process, the resin can be fully coated and dispersed in water, with a smaller particle size and better emulsion performance.
[0026] (3) The present invention mixes two kinds of polyethylene glycols (PEG4000 and PEG6000) with different molecular weights. This method can avoid the decrease of anticorrosive performance and emulsion stability due to too short molecular weight, and the excessive viscosity of the system due to too large molecular weight. If only PEG6000 is contained, the viscosity of the whole reaction system will increase sharply, resulting in incomplete reaction and failure to effectively disperse the epoxy resin. Moreover, the emulsion will be stratified and precipitated, and cannot be used.
[0027] (4) The water-based anticorrosive epoxy resin emulsion prepared by the present invention has good emulsion stability. When it is used to prepare a metal anticorrosion coating, the coating has strong adhesion, high hardness, excellent impact resistance, good water resistance, and excellent corrosion resistance and anti-corrosion performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] The drawings constituting part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation of the present invention. Obviously, for those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0029] Figure 1 1 is a particle size distribution diagram of the aqueous epoxy resin emulsion of Example 1 of the present invention and Comparative Examples 1 to 3;
[0030] Figure 2 is a graph showing the change in water absorption of coatings prepared from waterborne epoxy resin emulsions of Example 1 and Comparative Examples 1 to 3 over time;
[0031] Figure 3 It is a thermogravimetric analysis curve of the coating samples prepared by the aqueous epoxy resin emulsions of Example 1 and Comparative Examples 1 to 3 of the present invention;
[0032] Figure 4 It is the Nyquist plot of the coating prepared by the aqueous epoxy resin emulsion of Example 1 of the present invention and Comparative Examples 1 to 3;
[0033] Figure 5 It is the electrochemical test Bode plot (impedance modulus-frequency curve) of the coating prepared by the aqueous epoxy resin emulsion of Example 1 of the present invention and Comparative Examples 1 to 3;
[0034] Figure 6 It is the electrochemical test Bode plot (phase angle-frequency curve) of the coating prepared by the aqueous epoxy resin emulsion of Example 1 of the present invention and Comparative Examples 1 to 3;
[0035] Figure 7 It is the Tafel polarization curve of the coating prepared by the aqueous epoxy resin emulsion of Example 1 of the present invention and Comparative Examples 1 to 3;
[0036] Figure 8 It is a picture of the 200h salt spray test results of the coatings prepared with the aqueous epoxy resin emulsions of Example 1 and Comparative Examples 1 to 3 of the present invention. DETAILED DESCRIPTION
[0037] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0038] The technical solution of the present invention is further described below in conjunction with specific examples. In the following examples, E44 resin and PEG4000 and PEG6000 are all treated with water removal in advance.
[0039] Example 1
[0040] This embodiment provides a method for preparing a water-based anticorrosive epoxy resin emulsion.
[0041] (1) E44 resin and HMDI (4,4-dicyclohexylmethane diisocyanate) were placed in a three-necked flask, and the ratio of the molar amount of hydroxyl group of E44 resin to the molar amount of isocyanate group of HMDI was controlled to be 1:2; 0.2 wt% of boron trifluoride etherate (accounting for 0.2 wt% of the total mass of E44 resin, HMDI and boron trifluoride etherate) was added, and the temperature was raised to 90 °C for reaction for 3 h.
[0042] (2) Then, PEG4000 and PEG6000 were added in a mass ratio of 3:2, and the ratio of the total hydroxyl molar amount of PEG4000 and PEG6000 to the isocyanate molar amount of HMDI in step (1) was controlled to be 1:2. The temperature was lowered to 80°C and reacted for 2.5 hours to obtain a modified epoxy resin emulsifier E44-HMDI-PEG6000 / 4000.
[0043] (3) Weigh the modified epoxy resin emulsifier and E44 resin in a mass ratio of 1:5, place them in a three-necked flask, and stir them at 150 r / min for 0.5 h in a 70°C water bath using a dispersing disk to fully mix the sample. Then, add deionized water at 2000 r / min, and use the phase inversion method to prepare a water-based anticorrosive epoxy resin emulsion with a solid content of 30wt%, which has a white emulsion appearance.
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that HMDI is not added in this comparative example, and only PEG4000 is added. The specific preparation method is as follows:
[0046] Place E44 resin and PEG4000 in a three-necked flask, and control the molar ratio of the epoxy group of E44 resin to the hydroxyl group of PEG4000 to be 1:1; add 0.2wt% of boron trifluoride ether (to promote the ring-opening reaction of the epoxy group), heat to 80°C and react for 2.5h to obtain the modified epoxy resin emulsifier E44-PEG4000.
[0047] Weigh the modified epoxy resin emulsifier and E44 resin in a mass ratio of 1:5, place them in a three-necked flask, and stir them at 150 r / min for 0.5 h in a 70 ℃ water bath with a dispersing disk to fully mix the sample. Then add deionized water at 2000 r / min, and use the phase inversion method to prepare a water-based anticorrosive epoxy resin emulsion with a solid content of 30wt%, which has a white emulsion appearance.
[0048] Comparative Example 2
[0049] The difference between this comparative example and Example 1 is that HMDI is not added in this comparative example. The specific preparation method is as follows:
[0050] E44 resin and PEG4000 and PEG6000 in a mass ratio of 3:2 were placed in a three-necked flask, the molar ratio of the epoxy group of the E44 resin to the total hydroxyl group of PEG4000 and PEG6000 was controlled to be 1:1, 0.2wt% of boron trifluoride ether was added, the temperature was raised to 80°C and the reaction was carried out for 2.5h to obtain the modified epoxy resin emulsifier E44-PEG6000 / 4000.
[0051] Weigh the modified epoxy resin emulsifier and E44 resin in a mass ratio of 1:5, place them in a three-necked flask, and stir them at 150 r / min for 0.5 h in a 70°C water bath with a dispersing disk to fully mix the sample. Then add deionized water at 2000 r / min, and use the phase inversion method to prepare a water-based anticorrosive epoxy resin emulsion with a solid content of 30wt%, which has a white emulsion appearance.
[0052] Comparative Example 3
[0053] The difference between this comparative example and Example 1 is that only PEG4000 is added in this comparative example, and PEG6000 is not added. The specific preparation method is as follows:
[0054] (1) Place E44 resin and HMDI (4,4-dicyclohexylmethane diisocyanate) in a three-necked flask, and control the ratio of the molar amount of hydroxyl group of E44 resin to the molar amount of isocyanate group of HMDI to be 1:2; add 0.2 wt% of boron trifluoride etherate, raise the temperature to 90 °C and react for 3 h.
[0055] (2) Then add PEG4000, and control the ratio of the molar amount of hydroxyl group of PEG4000 to the molar amount of isocyanate group of HMDI in step (1) to be 1:2. Cool down to 80°C and react for 2.5h to obtain modified epoxy resin emulsifier E44-HMDI-PEG4000.
[0056] (3) Weigh the modified epoxy resin emulsifier and E44 resin in a mass ratio of 1:5, place them in a three-necked flask, and stir them at 150 r / min for 0.5 h in a 70°C water bath using a dispersing disk to fully mix the sample. Then, add deionized water at 2000 r / min, and use the phase inversion method to prepare a water-based anticorrosive epoxy resin emulsion with a solid content of 30wt%, which has a white emulsion appearance.
[0057] Comparative Example 4
[0058] The difference between this comparative example and Example 1 is that only PEG6000 is added in this comparative example, and PEG4000 is not added. The specific preparation method is as follows:
[0059] (1) Place E44 resin and HMDI (4,4-dicyclohexylmethane diisocyanate) in a three-necked flask, and control the ratio of the molar amount of hydroxyl group of E44 resin to the molar amount of isocyanate group of HMDI to be 1:2; add 0.2 wt% of boron trifluoride etherate, raise the temperature to 90 °C and react for 3 h.
[0060] (2) Then PEG6000 was added, and the ratio of the molar amount of the hydroxyl group of PEG6000 to the molar amount of the isocyanate group of HMDI in step (1) was controlled to be 1:2. The temperature was lowered to 80°C for reaction. During the reaction, the viscosity increased sharply, the stirring was insufficient, and the "climbing pole effect" occurred, resulting in incomplete reaction, making it difficult to effectively emulsify and disperse the epoxy resin. The prepared emulsion was stratified and precipitated, and further experiments could not be carried out. Therefore, the emulsion of this comparative example was not subjected to subsequent performance tests.
[0061] Test example
[0062] 1. Emulsion performance determination:
[0063] (1) Mechanical stability
[0064] Excellent mechanical stability is crucial for emulsions. In practical engineering applications, emulsions with good mechanical stability can ensure that they always maintain their initial size distribution during transportation and application. The mechanical stability of different emulsions was measured at a centrifugal speed of 6000 r / min for 10 minutes, as shown in Table 1.
[0065] Table 1 Mechanical stability of different emulsions
[0066]
[0067] As can be seen from Table 1, the mechanical stability of the emulsifier prepared by the reaction of epoxy group ring opening and PEG4000 is the worst, and it is obviously stratified at a speed of 6000 r / min. The E44-HMDI-PEG4000 emulsifier grafted with HMDI also showed stratification. This may be because the low molecular weight PEG4000 is used as a hydrophilic segment, which is not sufficient for the emulsification of epoxy resin. The emulsion is greatly affected by water and external forces. Under strong shear force, the particles collide with each other and the fusion particle size becomes larger, resulting in flocculation and sedimentation. The emulsifier containing PEG6000 as a hydrophilic segment (Example 1) did not show stratification of the epoxy resin after emulsification under mechanical stirring. This may be because the particle size of the resin after emulsification is small, the interaction force between particles is enhanced, and the droplet size can maintain a stable size even under mechanical stirring.
[0068] (2) Emulsion particle size
[0069] The particle size and distribution range of waterborne epoxy resin emulsion will affect the mechanical stability and storage stability of the emulsion. The particle size distribution of different waterborne epoxy resin emulsions was measured. The results are as follows: Figure 1 As shown in the figure, it can be seen that the particle size distribution of the emulsion of Comparative Example 2 is narrower, but the average particle size is larger than the average particle size of the emulsion of Example 1. The average particle sizes of the emulsions of Example 1 and Comparative Example 3 are concentrated in the range of 200-300 nm, which is smaller than the emulsion particle sizes of Comparative Examples 1 and Comparative Examples 2 that are not modified with HMDI.
[0070] (3) Storage stability
[0071] The sealed waterborne epoxy emulsion was naturally stored. During the storage period of 120 days, no precipitation or stratification occurred in the emulsions obtained in Example 1 and Comparative Examples 1 to 3, indicating that the storage stability was good.
[0072] 2. Performance determination of anti-corrosion coating:
[0073] Preparation of anti-corrosion coating: Weigh the water-based epoxy resin emulsion and curing agent (water-based modified amine curing agent HGH-300) of Example 1 and Comparative Examples 1 to 3 according to a solid mass ratio of 1:1, mix and place the mixed liquid in a vacuum box for vacuuming. After fully polishing the Q235 tinplate in a certain direction, rotate it 90 ° clockwise and continue polishing. After fully rinsing the polished Q235 tinplate with industrial alcohol, place it in an acetone solution for ultrasonic cleaning, and then air dry it naturally for use. Apply the vacuumized mixed liquid to the surface of the tinplate sheet with a coating thickness of 50 μm. The coating should be uniform during coating without obvious differences. Place it in a room temperature environment for curing for 24 hours and then place it in a 60 ℃ oven for curing for 12 hours.
[0074] (1) Coating adhesion performance
[0075] The coating adhesion grade can evaluate the adhesion between the coating and the substrate material, and is an important indicator for evaluating the performance of the coating. Whether it can firmly adhere to the substrate is the key to the long-term corrosion protection of the coating. According to the standard "Scratch Test for Paints and Varnishes" (GB / T 9286-2021), the lower the adhesion grade, the better the coating adhesion performance. The coating adhesion performance prepared by the coatings of Example 1 and Comparative Examples 1 to 3 is shown in Table 2.
[0076] Table 2 Coating adhesion performance test results
[0077]
[0078] From the results in Table 2, it can be seen that the coating formed by the modified emulsifier corresponding to the epoxy emulsion prepared using HMDI has a certain improvement in adhesion level compared with the coating formed by the unmodified emulsifier corresponding to the epoxy emulsion. Among them, the coating formed by the emulsion of Example 1 has the highest adhesion level, indicating that it has the best adhesion performance.
[0079] (2) Coating hardness measurement
[0080] The coating film hardness is a key indicator of the coating's resistance to the external environment's local pressure. The greater the hardness, the longer the coating's service life and the stronger its durability. The coating hardness was measured using the coating pencil hardness test method (test standard: GB / T 6739-2022). The results of pencil hardness tests for different coatings are shown in Table 3.
[0081] Table 3 Coating pencil hardness test results
[0082]
[0083] It can be seen from Table 3 that the coating hardness formed by the emulsion using E44-HMDI-PEG6000 / 4000 emulsifier is 5H, which has the highest coating hardness.
[0084] (3) Determination of coating impact resistance
[0085] The impact resistance of the coating film is the ability of the coating to resist damage under the action of gravity in the external environment without cracking or peeling off from the base material. The test standard is GB / T 6739-2022, and the test results are shown in Table 4.
[0086] Table 4 Test results of coating impact resistance
[0087]
[0088] It can be seen from Table 4 that the impact strength of E44-HMDI-PEG6000 / 4000 reaches 50 cm, which is related to its good toughness and strength. However, the impact strength of the coating obtained by using the emulsions of Comparative Examples 1 to 3 is lower.
[0089] (4) Determination of coating water resistance:
[0090] The water resistance of the coating directly reflects the coating's resistance to water. The water absorption rate of different coatings changes over time. Figure 2As shown in the figure, it can be seen that the water absorption rate of different coatings has roughly the same trend over time: the water absorption rate is linearly correlated with time in the first 12 hours, and after 12 hours, as the pores of the coating are filled with water, the water absorption rate has no significant change. The water absorption rate of the coating prepared using the emulsion of Example 1 is about 68% lower than that of the coating prepared using the emulsion of Comparative Example 1, and the water absorption rate of the coating of Example 1 is the lowest, with a water absorption rate of less than 6% in 24 hours.
[0091] (5) Thermogravimetric analysis
[0092] Thermogravimetric analysis is to measure the relationship between the mass of the analyzed sample and the temperature change, which can be used to determine the thermal stability of the material. The thermogravimetric temperature rise range is 25-600 ℃. Figure 3 It can be seen that in the temperature range of 25-260 ℃, the mass loss rate of the samples after drying the emulsions of Example 1 and Comparative Examples 1~3 is less than 5%. As the temperature continues to rise, in the temperature range of 260℃-450℃, the mass loss of the four materials is significantly aggravated. This is because the rupture of the carbon-nitrogen monomer formed by the reaction of the epoxy group with the amine hydrogen in the curing agent causes the cross-linking structure to be destroyed, especially the mass loss of the water-based epoxy coating using the unmodified emulsifier begins to occur first, and the rate of decrease of the sample mass with temperature change is also the fastest. The water-based epoxy coating using the modified emulsifier of Example 1 and Comparative Example 3 has a significant decrease at about 310 ℃, because the six-membered ring in the isocyanate in the modified emulsifier improves the heat resistance of the epoxy resin after curing. The temperature continues to rise, and in the temperature range of 450℃~600℃, the residual mass of the sample tends to be stable. Among them, the residual mass of the coating using the modified emulsifier of Example 1 and Comparative Example 3 is about 10%, and the residual mass of the coating of Comparative Example 1 and Comparative Example 2 is about 7%. It can be seen that the introduction of HMDI can further improve the thermal stability of the coating.
[0093] (6) Electrochemical testing
[0094] EIS testing can evaluate the corrosion resistance of coatings without affecting the performance of coatings, so electrochemical impedance spectroscopy is used to study the electrochemical behavior and anti-corrosion performance of coatings in NaCl solution. The electrochemical test results of different coatings in 3.5wt% NaCl solution are shown in Figure 2. Figure 4 As shown, Figure 4is the Nyquist plot of different coatings. It can be seen from the figure that within the frequency range, only one capacitive arc appears, which means that the coating blocks the electrolyte solution and does not come into contact with the metal substrate to cause corrosion in the initial stage of immersion. The capacitive arc radius can characterize the ability of the coating to hinder ion penetration. The unmodified coating has the smallest capacitive arc radius, and the modified coating has a significantly larger capacitive arc radius than the unmodified coating. As the molecular weight of PEG increases, the coating capacitive arc radius increases accordingly. The larger the capacitive arc radius, the stronger the coating's ability to resist ion penetration, which means that the coating has a higher density and better corrosion resistance. It can be seen that the water-based epoxy coating prepared using the emulsion of Example 1 has the best corrosion resistance.
[0095] The impedance value corresponding to the low-frequency region can reflect the protective performance of the coating. Figure 5 It can be seen that at the initial stage of immersion, the impedance modulus values (|Z| 0.01Hz ) is 10 4 Ω·cm 2 , the coating of Example 1 has |Z| 0.01Hz For 10 6 Ω·cm 2 , which is two orders of magnitude higher. Figure 6 It can also be seen from the Bode diagram (phase angle-frequency curve) that the phase angle of the coating of Comparative Example 1 is only about 58°, while the phase angle of the coating of Example 1 reaches about 83° in the high frequency region and remains within a larger frequency range.
[0096] Tafel polarization test can obtain corrosion potential, corrosion current density and corrosion rate by destroying the coating surface and applying large voltage and current. The test results are as follows: Figure 7 It is generally believed that the corrosion current density (I corr ) is smaller, the corrosion potential (E corr ) is larger, the better the corrosion resistance of the coating is, and the higher the slow-release efficiency (η). Figure 7 It can be seen that the corrosion resistance of the coating of Example 1 is significantly better than that of the coatings of Comparative Examples 1 to 3.
[0097] Corrosion rate corr (mm / year) is calculated by the following formula (3-1):
[0098] (3-1)
[0099] Where A is the molecular weight of Q235 tinplate (55.85 g / mol); ρ is the density of Q235 tinplate (7.85 g / cm 3 ); n is 2; F is the Faraday constant (F=96485 C / mol=26.8 A·h); I corrCorrosion current density.
[0100] The corrosion inhibition efficiency (η) is calculated by the following formula:
[0101] ;
[0102] in, The corrosion current density of the coating prepared by the emulsion of Comparative Example 1 or Comparative Example 2; The corrosion current density of the coating prepared for Comparative Example 3 or Example 1 (Comparative Example 1 corresponds to Comparative Example 3, and Comparative Example 2 corresponds to Example 1).
[0103] The test results are summarized in Table 5.
[0104] Table 5 Tafel test results of different coatings
[0105]
[0106] The corrosion potential can indicate the corrosion resistance of the material. The more positive the potential, the less likely the material is to undergo spontaneous corrosion, while the corrosion current density is directly related to the corrosion rate. corr The larger the value, the more serious the corrosion. corr A smaller value indicates that the material has better corrosion resistance. The corrosion rate can be further obtained through the corrosion potential and corrosion current density. corr The smaller the value, the better the corrosion resistance of the coating. As can be seen from Table 5, the corrosion potential of the coating prepared using the emulsion of Example 1 is -0.4662 V and the corrosion current density is 1.554×10 -6 A / cm 2 , the corrosion rate is 0.01807 mm / year, which are both lower than those of the coatings in the comparative examples. This indicates that the corrosion resistance of the coating in Example 1 is significantly better than that of the coatings in comparative examples 1 to 3.
[0107] (7) Salt spray test
[0108] The salt spray test can simulate the corrosion reaction of metal materials exposed to high humidity, high salt, and high oxygen content in the atmosphere, and can evaluate the corrosion resistance of the coating in a short time. According to GB / T 10125-2021 (Artificial Atmosphere Corrosion Test Salt Spray Test), the neutral salt spray test is carried out. The solution sprayed in the salt spray box is 50g / L NaCl solution with a pH value of 7.0, and the temperature in the box is maintained at 25±2℃. Figure 8 The 200h salt spray test results of the coatings prepared from the aqueous epoxy resin emulsions of Example 1 and Comparative Examples 1 to 3 are shown in FIG. Figure 8As can be seen in a, the coating of comparative example 1 has a large amount of corrosive substances accumulated and overflowed at the scratches, and covered the coating surface; even at the non-scratched areas, there are bulges, and even overflow of corrosive substances. The coatings of comparative examples 2 and 3 also have obvious rust phenomena ( Figure 8 b and c), while the waterborne epoxy coating of Example 1 has less accumulation of corrosive substances at the scratches and no obvious diffusion phenomenon ( Figure 8 This is because the denser coating has better barrier properties and corrosion resistance, which hinders the oxidation of water, chloride ions, etc. at the scratches.
[0109] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a water-based anticorrosive epoxy resin emulsion, characterized in that: The steps include: A bisphenol A type liquid epoxy resin and a diisocyanate compound are heated to react under the action of a catalyst, and then polyethylene glycol is added to react to obtain a modified epoxy resin emulsifier; the polyethylene glycol is a mixture of PEG4000 and PEG6000, and the mass ratio of PEG4000 to PEG6000 is 3:(1-3); the ratio of the hydroxyl molar amount of the bisphenol A type liquid epoxy resin, the isocyanate molar amount of the diisocyanate compound, and the hydroxyl molar amount of the polyethylene glycol is 1:(1.8-2.2):(0.9-1.5); the added amount of the catalyst is 0.2-0.5wt%; The modified epoxy resin emulsifier and bisphenol A type liquid epoxy resin are heated and mixed, and then water is added by a phase inversion method to prepare a water-based anticorrosive epoxy resin emulsion.
2. The preparation method according to claim 1, characterized in that The bisphenol A type liquid epoxy resin is selected from one or both of epoxy resin E44 and epoxy resin E51; the diisocyanate compound is selected from one or more of toluene diisocyanate, isophorone diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate or 4,4-dicyclohexylmethane diisocyanate; and the catalyst is selected from one or more of triphenylphosphine, boron trifluoride complex, tetrafluoroboric acid solution or tin tetrachloride.
3. The preparation method according to claim 2, characterized in that: The bisphenol A type liquid epoxy resin is selected from epoxy resin E44; the diisocyanate compound is selected from 4,4-dicyclohexylmethane diisocyanate, and the catalyst is selected from boron trifluoride etherate.
4. The preparation method according to claim 1, characterized in that: The reaction temperature of bisphenol A type liquid epoxy resin and diisocyanate compound is 80~100℃, and the reaction time is 2~8h.
5. The preparation method according to claim 1, characterized in that: In the step of adding polyethylene glycol to react and obtain the modified epoxy resin emulsifier, the reaction temperature is 70-90° C. and the reaction time is 2-8 hours.
6. The preparation method according to claim 1, characterized in that: In the step of heating and mixing the modified epoxy resin emulsifier and the bisphenol A type liquid epoxy resin, the mass ratio of the modified epoxy resin emulsifier to the bisphenol A type liquid epoxy resin is 1:(4-6).
7. The preparation method according to claim 1, characterized in that: The solid content of the water-based anticorrosive epoxy resin emulsion is 30-50wt%.
8. The aqueous anticorrosive epoxy resin emulsion prepared by the preparation method according to any one of claims 1 to 7.
9. The use of the water-based anticorrosive epoxy resin emulsion according to claim 8, characterized in that: The application is application in preparing metal anti-corrosion coating, and the method for preparing metal anti-corrosion coating is as follows: The water-based anti-corrosion epoxy resin emulsion and the curing agent are evenly mixed and then coated on the surface of the metal substrate. After curing, the metal anti-corrosion coating is obtained.
Citation Information
Patent Citations
Single-component water-based epoxy resin emulsion and preparation method thereof
CN102675861A
Water-borne epoxy resin emulsion for heavy anti-corrosion coating as well as preparation method and application of water-borne epoxy resin emulsion
CN113278346A